THE ROLE OF MEDICAL PERSONNEL IN THE CLICHE OF MATERNITY AND CHILD PROTECTION IN UZBEKISTAN - Toshtemirova Nigora Dilshodovna (Web of Journals Publishing, 2024)
Uzbekistan is one of the countries with a high birth rate in the Central Asian region, and most of the population consists of children. This requires special attention to the protection of motherhood and the child.
Keywords: Uzbekistan, Healthcare, pediatrician, obstetrician, gynecologist, QVP, UNESCO, UNFPA, International organizations, medical institutions, staff, consulting center.